Osmium on Chelate Resin: Nonvolatile Catalyst for the Synthesis of Diols from Alkenes - Monguchi, Yasunari; Wakayama, Fumika; Takada, Hitoshi; Sawama, Yoshinari; Sajiki, Hironao (Synlett, 2015)
Osmium tetraoxide (OsO4) was immobilized on a commercially available chelate resin DIAION CR11 (CR11) just by simply immersing it in a methanol solution of OsO4 at room temperature. The resulting purple solid, 5% Os/CR11, indicated no volatility, and effectively catalyzed the oxidation of various alkenes to the corresponding diols.
Keywords: chelate resin; diols; osmium; oxidation; supported catalyst